2016
DOI: 10.1155/2016/5958382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Its Associated Risk Factors among 34,111 HAART Naïve HIV-Infected Adults in Dar es Salaam, Tanzania

Abstract: Background. Elevated blood pressure has been reported among treatment naïve HIV-infected patients. We investigated prevalence of hypertension and its associated risk factors in a HAART naïve HIV-infected population in Dar es Salaam, Tanzania. Methods. A cross-sectional analysis was conducted among HAART naïve HIV-infected patients. Hypertension was defined as systolic blood pressure (SBP) ≥ 140 mmHg and/or diastolic blood pressure (DBP) ≥ 90 mmHg. Overweight and obesity were defined as body mass index (BMI) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
22
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
11
22
5
Order By: Relevance
“…This observation corroborates with previous studies of Lichtenstein et al (2010), PefuraYone et al (2011), Ekali et al (2013), Muhammad et al (2013) and Njelekela et al (2016), which revealed a higher incidence of hypertension in patients on cART. Contrarily, the findings of other studies of Agrawal et al (2015) indicated no disparity in the prevalence of hypertension between patients on cART and cARTnaïve patients.…”
Section: Resultssupporting
confidence: 93%
“…This observation corroborates with previous studies of Lichtenstein et al (2010), PefuraYone et al (2011), Ekali et al (2013), Muhammad et al (2013) and Njelekela et al (2016), which revealed a higher incidence of hypertension in patients on cART. Contrarily, the findings of other studies of Agrawal et al (2015) indicated no disparity in the prevalence of hypertension between patients on cART and cARTnaïve patients.…”
Section: Resultssupporting
confidence: 93%
“…The hypertension occurrence was considerably greater in patients on cART as compared to cART-naïve patients. This observation corroborates with previous studies of Lichtenstein et al [15], Pefura Yone et al [16], Ekali et al [17], Muhammad et al [11] and Njelekela et al [18], which revealed a higher incidence of hypertension in patients on cART. Contrarily, the findings of other studies of Agrawal et al [19] indicated no disparity in the prevalence of hypertension between patients on cART and cARTnaïve patients.…”
Section: Discussionsupporting
confidence: 93%
“…Abacavir did not elevate the risk of hypertension, compared to non-abacavir ART, and only elevated the risk among men and older adults who visited tertiary hospitals in urban areas. Old age 24 25 and being male 25 were similar risk factors of hypertension among PLWH in other studies. Nevertheless, while financial status or accessibility to healthcare was not considered in the model, this study found that PLWH who visit institutions with specialty doctors in urban areas were more prone to being diagnosed with hypertension.…”
Section: Discussionsupporting
confidence: 78%